Pengomposan Limbah Pertanian Sebagai Upaya Mengatasi Pencurian Humus Di Taman Hutan Raya Bukit Barisan Kabupaten Karo - Malrizky Fachmy; Budi Utomo; Nurzainah Ginting (Program studi Kehutanan USU, 2015)
Taman Hutan Raya avoid the problem of where humus stolen by farmers in a jungle that was a native Kabupaten Karo. The purpose of this research was to reduce and overcome theft humus in Taman Hutan Raya Bukit Barisan. The study was done in September-December 2014 in the village Dolat Rayat Kabupaten Karo using several treatment. This research using three treatment and three remedial. The treatment was 1) the rumen treatment, 2) tempe, tape with kefir treatment, 3) mole fruit with vegetables, with the parameters that could be tested in temperature, the ratio of pH and C/N. The result of research showed that the provisions of treatment of all parameters temperature and pH getting results did not affect real (Fhit 3.5<Ftabel 5.143) and (Fhit 0.05<Ftabel 5.143) while the treatment in all the provision of real results on parameters of ratio C/N (Fhit 47.89>Ftabel 5.143). the conclusions from the results of this research is treatment tempe, tape with kefir and treatment mole fruit with vegetable getting good results which is in form of temperature, pH and the C/N ratio.Key word: composting, theft of humus, agricultur waste, the temperature, pH, C/N ratio